2012
DOI: 10.1111/j.1365-294x.2012.05468.x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations on orchid recruitment: not a simple picture

Abstract: Mycorrhizal fungi have substantial potential to influence plant distribution, especially in specialized orchids and mycoheterotrophic plants. However, little is known about environmental factors that influence the distribution of mycorrhizal fungi. Previous studies using seed packets have been unable to distinguish whether germination patterns resulted from the distribution of appropriate edaphic conditions or the distribution of host fungi, as these cannot be separated using seed packets alone. We used a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
116
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 61 publications
3
116
1
2
Order By: Relevance
“…Essentially all temperate orchids are terrestrial, but most orchids inhabit tropical forests and over 80% of those are epiphytes. All orchids rely on fungi for germination and carbon capture in the protocorm stage, and in many taxa this mycorrhizal association remains obligate for life [3]. Orchids in more than 30 small mycoheterotrophic lineages have lost all photosynthetic capacity and rely entirely on fungi for energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Essentially all temperate orchids are terrestrial, but most orchids inhabit tropical forests and over 80% of those are epiphytes. All orchids rely on fungi for germination and carbon capture in the protocorm stage, and in many taxa this mycorrhizal association remains obligate for life [3]. Orchids in more than 30 small mycoheterotrophic lineages have lost all photosynthetic capacity and rely entirely on fungi for energy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Además de factores bióticos como la competencia y otras interacciones como es la presencia de hongos micorrízicos apropiados, sin los cuales la germinación de las semillas de orquídeas es imposible (Winkler et al 2009). Otros factores no identificados relacionados con las condiciones del microhábitat pueden limitar la ditribución y la abundancia de las orquídeas (McCormick et al 2012, Otero et al 2013. Los valores mínimos y máximos de las variables analizadas representan las condiciones extremas en que se desarrollan los individuos de E. pyriformis muestreados en la Reserva Ecológica Los Pretiles.…”
Section: Discussionunclassified
“…Entre las características del forófito de mayor influencia está la arquitectura arbórea (FloresPalacios & Ortíz-Pulido 2005, Otero et al 2007, Winkler & Hietz 2001, las características físicas y químicas de la corteza, su estabilidad, la disponibilidad de área colonizable y la cobertura vegetal (Callaway et al 2002, Maldonado & Mondragón-Chapano 2007. Estas características junto a las condiciones microclimáticas y los requerimientos ecofisiológicos de las epífitas puede limitar la distribución y abundancia de las mismas (Maldonado & Mondragón-Chapano 2007, McCormick et al 2012.…”
unclassified
“…Studies on the interaction of plants, mycorrhizae and soil types are still scarce. However, McCormick et al (2012) studied the relationship of germination and protocorm development of three species of terrestrial orchids under different soil compositions and in the presence or absence of mycorrhizae. The authors concluded that the establishment and development of orchids depends much more on the abundance and distribution of mycorrhizae in the soil than on the presence of nutrients in adequate concentrations.…”
Section: Resultsmentioning
confidence: 99%